Fine Arts and its Essence, Species and Genres - Zokirova Shahlokhon (Global Scientific Publishing, 2023)
Fine Arts is a phrase used to refer to a wide variety of artistic works such as fine art, sculpture, painting, printing, photography and installation art. Its purpose is to demonstrate concepts, feelings and manifestations of the world through aesthetic elements that provoke and interest the viewer. In this article, we will study the essence, types and genres of Fine Art.
Keywords: Fine Art; Contemporary Art; political or social